One-year results of the treatment of critical lower limb ischemia with indirect revascularization methods - B. S. Sukovatykh; L. N. Belikov; A. Yu. Orlova; M. B. Sukovatykh; A. O. Rodionov (Вестник хирургии имени И.И. Грекова)
The OBJECTIVE was to compare the efficiency of autologous bone marrow cell implantation and lumbar sympathectomy in the treatment of chronic critical lower limb ischemia. MATERIAL AND METHODS. The complex examination and treatment of 66 patients with critical lower limb ischemia, divided into 2 statistically homogeneous groups, was analyzed. The first group underwent sympathectomy, and the second – autologous bone marrow cell transplantation.RESULTS. After 1 year, in patients of the second group, compared with the first, the clinical status increased by 51.5 %, the number of amputations decreased by 3 %, the physical component of health increased by 7.9 %, the psychological component – by 17.7 %.CONCLUSION. The autologous bone marrow cell transplantation was pathogenetically substantiated and effective.